2020
DOI: 10.1149/1945-7111/ab927c
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion-Induced Microstructural Variability Affects Transport-Kinetics Interaction in PEM Fuel Cell Catalyst Layers

Abstract: The ionomer, which is responsible for proton transport, oxygen accessibility to reaction sites, and binding the carbon support particles, plays a central role in dictating the catalyst layer performance. In this work, we study the effect of ionomer distribution owing to the corrosion induced degradation mode in the catalyst layer based on a combined mesoscale modeling and experimental image-based data. It is observed that the coverage of the ionomer over the platinum-carbon interface is heterogeneous at the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…16 In the CL fabrication, the carbonsupported Pt particles are mixed with the ionomer solution and selforganize into an extremely complex structure with an approximately 2-3 nm ionomer film that covers the Pt surface. 17,18 Goswami et al 19 found that the ionomer layer's coverage and thickness on the carbonsupported Pt particles are heterogeneous, which affected CL performance. The neutron scattering (NR) and surface X-ray scattering (SXS) technologies 20,21 revealed that the hydrophobic fluorocarbon groups were the main species adsorbed on the Pt (111) surface.…”
Section: List Of Symbolmentioning
confidence: 99%
“…16 In the CL fabrication, the carbonsupported Pt particles are mixed with the ionomer solution and selforganize into an extremely complex structure with an approximately 2-3 nm ionomer film that covers the Pt surface. 17,18 Goswami et al 19 found that the ionomer layer's coverage and thickness on the carbonsupported Pt particles are heterogeneous, which affected CL performance. The neutron scattering (NR) and surface X-ray scattering (SXS) technologies 20,21 revealed that the hydrophobic fluorocarbon groups were the main species adsorbed on the Pt (111) surface.…”
Section: List Of Symbolmentioning
confidence: 99%
“…This process was completed on several different representative volume elements (RVEs) and FIB-SEM geometries to obtain these curves based on work from Goswami. 90 The RVE that best represented the geometry in question while allowing for acceptable run times was the 90x90x(z) cubic voxel geometry, where z represents the number of slices in the FIB-SEM dataset for that geometry. For these simulations, z ranges between 90 and 185.…”
Section: Computational Methodologymentioning
confidence: 99%
“…The performance model of the CCL solves the multiple physico-chemical transport mechanisms in a volume-averaged sense as enumerated in Goswami et al 50 The assumptions include steady-state operation of the fuel cell under isothermal conditions. In addition, the model is approximated as a single phase such that the byproduct water is existent only in the gaseous phase.…”
Section: Mathematical Descriptionmentioning
confidence: 99%